Engineered elastin-like polypeptides: An efficient platform for enhanced cancer treatment - Jiang, Aiguo; Guan, Xinqiang; He, Lianping; Guan, Xingang (Frontiers in Pharmacology, 2023)
Drug delivery systems (DDSs) have recently gained widespread attention for improving drug loading and delivery efficiency in treating many cancers. Elastin-like polypeptides (ELPs) are synthetic peptides derived from a precursor of elastin (tropoelastin), reserving similar structural and physicochemical properties. ELPs have gained a variety of applications in tissue engineering and cancer therapy due to their excellent biocompatibility, complete degradability, temperature-responsive property, controllable sequence and length, and precisely tuned structure and function. ELPs-based drug delivery systems can improve the pharmacokinetics and biodistribution of therapeutic reagents, leading to enhanced antitumor efficacy. In this review, we summarize the recent application of ELPs in cancer treatment, focusing on the delivery of functional peptides, therapeutic proteins, small molecule drugs, and photosensitizers.